The Effect Of Stock Price Volatility, Stock Trading Volume And Market Capitalization On Stock Returns With The Moderation Of The Company's Reputation In Banking Sector Companies That Listed On The Indonesia Stock Exchange - Qori Fadla Ajmilia; Nisrul Irawati; Syahyunan (Journal of Business Management, 2026)
This study aims to analyze the influence of stock price volatility, trading volume, and market capitalization on stock returns in banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period. In addition, this study also examines the role of company reputation as a moderation variable. The research sample was determined using the purposive sampling technique, so that 22 companies were obtained as a research sample. The analysis method used in this study is Moderate Regression Analysis (MRA). The results of the study show that stock price volatility has a positive and significant effect on stock returns, stock trading volume has a negative but insignificant effect on stock returns. In addition, market capitalization has a negative but not significant effect on stock returns. Other results show that the company's reputation moderates the effect of stock price volatility on stock returns negatively and significantly, then the company's reputation does not moderate the effect of stock trading volume on stock returns positively and significantly, and the company's reputation also does not moderate the effect of market capitalization on returns stocks negatively and significantly. These findings imply that the management of stock price volatility and the development of a company's reputation need to be considered strategically in order to increase stock returns, while trading volume and market capitalization require a more comprehensive analytical approach in investment decision-making in banking companies